Frequency and clinical associations of anti-chromo antibodies in connective tissue disease. Issue 10 (October 1994) - Soriano, E; Whyte, J; McHugh, N J
Abstract : OBJECTIVES–To assess the frequency and clinical associations of anti-chromo antibodies in connective tissue disease and to study their relationship to anti-centromere autoreactivity. METHODS–Anti-chromo and anti-centromere antibodies (ACA) were measured by immunoblotting in 50 patients with systemic sclerosis (SSc) and 58 connective tissue disease controls. Common epitopes on centromere and chromo antigens were sought using affinity-purified antibodies from immunoblots. RESULTS–Anti-chromo antibodies were detected in three of 32 sera with ACA and no controls. The three patients with anti-chromo antibodies had limited cutaneous SSc, and two had erosive arthritis. No cross-reactivity between chromo or centromere-related proteins was demonstrated. CONCLUSIONS–Anti-chromo antibodies form a rare autoantibody specificity that may identify an overlap group of patients with SSc and arthritis. Chromo and centromere antigens are associated but immunologically distinct autoimmune targets. Whether they localise to the same chromosomal site remains unknown.